1998
DOI: 10.1080/01140671.1998.9514065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frost during grain filling on wheat yield and grain structure

Abstract: A late frost occurred in the Southland region of New Zealand in November 1995 when many winter wheat (Triticum aestivum L.) crops were at early grain fill, and resulted in a large number of insurance claims for frost damage. In this study, frost damage was characterised. Spikes in affected crops were sharply tapered from a point half to two-thirds from their bases. Grains were as much as 80% lighter in upper parts of affected spikes. Overall yield losses as a result of frost of between 13 and 33% were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…Frost affects the biological processes of grain filling and thus the grain weight remains low, the grain is of poor quality and in some cases only empty hulls remain. Occurrence of frost has resulted in formation of shrivelled and shrunken wheat grains and in less severe cases blistering of the grain surface and thus, low grain weight during the grain filling stage (Cromey et al, 1998). Cromey et al (1998) suggested that the damage was due to death of outer tissues of grains, most damage occurring in the testa and pericarp and to some extent in the endosperm.…”
Section: Autumn Frostsmentioning
confidence: 99%
See 3 more Smart Citations
“…Frost affects the biological processes of grain filling and thus the grain weight remains low, the grain is of poor quality and in some cases only empty hulls remain. Occurrence of frost has resulted in formation of shrivelled and shrunken wheat grains and in less severe cases blistering of the grain surface and thus, low grain weight during the grain filling stage (Cromey et al, 1998). Cromey et al (1998) suggested that the damage was due to death of outer tissues of grains, most damage occurring in the testa and pericarp and to some extent in the endosperm.…”
Section: Autumn Frostsmentioning
confidence: 99%
“…Occurrence of frost has resulted in formation of shrivelled and shrunken wheat grains and in less severe cases blistering of the grain surface and thus, low grain weight during the grain filling stage (Cromey et al, 1998). Cromey et al (1998) suggested that the damage was due to death of outer tissues of grains, most damage occurring in the testa and pericarp and to some extent in the endosperm. The pericarp and testa were crushed and the dead cells were in a loose arrangement in frosted grains.…”
Section: Autumn Frostsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frost can cause death of anthers and embryos (Cromey et al 1998), resulting in sterility of florets and whole spikelets (Marcellos and Single 1984;Al-Issawi et al 2013), thereby impacting yield. Visible symptoms may include bleaching of awns and anthers, which become pale yellow or white and shrivelled.…”
mentioning
confidence: 99%